Soil management - Streeter, Lyman Bradley (My University, 1907)
Introduction: For the last fifty years the farmers of Kansas have been continually taking crops from the soil with little thought of returning anything to it. Likewise, little attention has been given to the rotation of crops and proper methods of tillage. Usually the only object in cultivation has been to kill weeds and consequently, many years, the yields have been smaller than they would have been if the field had had the proper treatment. Planting a field continuously to the same crop for twenty-five years or more has often largely exhausted certain forms of plant food that are essential to the growth and developement of that crop. This practice up to the present time has been yielding fairly good crops for the reason thtt the soil was new and rich in the necessary plant food elements. At present, however the older lands are becomming so exhausted that something must be done to stop this terrible drain upon the fertility of the soil. The average farm in Kansas may be made to produce perhaps half as much more than it is now producing by the application of the best methods of soil management. The great question that confronts the farmer of today is how to build up and maintain the soil fertility, how to conserve the moisture, and how to prevent the soil from blowing and washing.
Citation: Streeter, Lyman Bradley. Soil management. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Soil Management; Improving Soil Fertility; Crop Rotation; Soil Quality; Theses